Burden and trend of cardiovascular diseases among people under 20 years in China, Western Pacific region, and the world: An analysis of the global burden of disease study in 2019 - Zhang, Yue; Lin, Changjian; Liu, Ming; Zhang, Wei; Xun, Xiaoyun; Wu, Jinyi; Li, Xiaopan; Luo, Zheng (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Cardiovascular disease (CVD) is a global public health concern, but its disease burden and trend have been poorly studied in ages younger than 20 years. This study aimed to fill this gap by evaluating the CVD burden and trends in China, Western Pacific Region and the world from 1990 to 2019. Methods: We applied GBD 2019 analytical tools to compare CVD incidence, mortality, prevalence, the years lived with disability (YLDs), the years of life lost (YLLs) and disability-adjusted life-years (DALYs) at ages younger than 20 years from 1990 to 2019 in China, Western Pacific Region and World. Trends of disease burden between 1990 and 2019 were evaluated using the average annual percent change (AAPC) and the 95% uncertainty interval (UI) were reported. Results: Globally in 2019, there were 2.37 (95% UI: 1.82 to 3.05) million incident CVD, 16.85 (95% UI: 12.56 to 22.03) million prevalent CVD and 74386.73(95% UI: 64543.82 to 86310.24) deaths due to CVD before 20 years of age. The trends for DALYs decreased among children and adolescents in China, Western Pacific Region and the world (AAPC=−4.29%, 95%CI: −4.38% to −4.20%; AAPC=−3.37%, 95%CI: −3.48% to −3.26%; AAPC=−2.17%, 95%CI: −2.24% to −2.09%; P<0.001, respectively) between 1990 and 2019. With the increase of age, the AAPC of mortality, YLLs and DALYs values showed a notable downward trend. The AAPC of mortality, YLLs and DALYs in females were significantly greater than those in males. For all subtypes of CVD, the AAPC values showed a downward trend, with the largest reduction observed for stroke. From 1990 to 2019, declines in the DALY rate for all CVD risk factors were observed, with a significant decrease in environmental/occupational risk factors. Conclusion: Our study shows a decline in burden and trend at ages younger than 20 years, which reflects the success in reducing disability, premature death and early incidence of CVD. More effective and targeted preventive policies and interventions aimed at mitigating preventable CVD burden and addressing risk factors from childhood are urgently needed.